Gefühl und Gedächtnis in der Moderne - Johannes Görbert (Recherches Germaniques)
The model analysis applies the systematic theories of the lyric by Klaus W. Hempfer, Dieter Lamping and Rüdiger Zymner to Bertolt Brecht’s 1920 poem Erinnerung an die Marie A. (Remembering Marie A.) and thus to one of the most famous poems of classical modernism. It examines first the poem’s discourse together with some testimonies of its reception and proves that the language of Erinnerung an die Marie A. almost paradigmatically fulfils Zymner’s definition of poetry as “display of linguistic mediality” and “catalyst of aesthetic evidence”. Subsequently, the analysis puts Lamping’s criterion of the individual speech as well as Hempfer’s premises of an asymmetry between the speaker and the recipient and a fiction of performativity with an I-Here-Now-Deixis in poems to the test. These assumptions can both be supported and problematized by the example of Erinnerung an die Marie A., the latter above all by the indicated dialogue of the text and its position in Brecht’s collection of poems in his Hauspostille. Finally, the analysis relates Zymner’s functional typology of poetry to Brecht’s poem. All in all, this model analysis both systematizes previous research results on a lyrical meta-level and generates new insights.